Biomechanical analysis of a heavy load calf muscle rehabilitation exercise in persons with Achilles tendinosis - Johnson, Shelley Elizabeth (Auckland University of Technology, 2008)
The aim of this dissertation was firstly to determine the efficacy of heavy-load eccentric calf muscle (HLECM) training for Achilles tendinosis through a review of the current scientific literature. The second objective was to assess the biomechanics of the HLECM training technique via an experimental study of calf muscle activity in individuals with Achilles tendinosis. Achilles tendinosis is a chronic painful condition of the Achilles tendon. HLECM training has been developed as a popular form of conservative treatment for Achilles tendinosis. However, there is little research investigating the biomechanics of the HLECM training technique. A key component of the original technique is the inclusion of a straight and bent knee condition, proposed to activate the gastrocnemius and soleus muscles respectively. Despite widespread use of these specific conditions in subsequent research, there is no evidence to suggest this selective muscle activation occurs in persons with Achilles tendinosis. A literature review was conducted to determine the effectiveness of the HLECM training protocol for Achilles tendinosis and to also compare its efficacy against other conservative treatment methods. The biomechanical study was a repeated measure, cross-sectional design. A critical review of 8 studies was undertaken assessing methodological quality through a Cochrane scoring system. A qualitative analysis to establish the level of evidence for the efficacy of HLECM training was also undertaken. For the biomechanical study, participants (n=18) diagnosed with Achilles tendinosis were recruited. Gastrocnemius and soleus muscle activity during the straight and bent knee conditions of the HLECM training technique, and during a maximum voluntary contraction (MVC), were determined through use of electromyography (EMG). The data was expressed as a percentage of the MVC for each muscle in each condition. Participant data sourced from a previous study, (Potts, 2005), served as controls (n=18). A three-factor repeated measures ANOVA was performed. The within subject factors were joint position and muscle, while group (experimental or control) was the between subjects factor. The critical review demonstrated a positive response to HLECM training but also highlighted the presence of inconsistent inclusion and exclusion criteria, variable outcome measures and alterations to the original HLECM protocol methodology. These factors contributed to the difficulty in comparing the outcomes of studies and hence the efficacy of the intervention. Participants with Achilles tendinosis demonstrated significantly higher EMG activity of both the gastrocnemius and soleus muscles in all conditions. There was a significant effect of joint position on the total group (the experimental and control group combined). The gastrocnemius muscle was significantly more active in the straight knee condition and the soleus muscle in the bent knee condition. There is moderate evidence of the efficacy of HLECM training for the treatment of Achilles tendinosis. The mechanisms of pain alleviation and return to functional activity through this use of this regime remain unclear. There is evidence to suggest there is a selective activation of the gastrocnemius and soleus muscles of the calf during the straight and bent knee conditions of the HLECM training protocol as described by Alfredson et al. (1998). Furthermore, the presence of Achilles tendinosis pathology influences calf muscle activity levels during performance of this training protocol.
Keywords: Ankle and heel function; Tendinosis; Alfredson; Electromyography; Tendon function; Muscle activity